POTENTIAL OF RHIZOBIUM SPECIES TO ENHANCE GROWTH AND FODDER YIELD OF MAIZE IN THE PRESENCE AND ABSENCE OF L-TRYPTOPHAN - M. A. Qureshi; H. Shahzad; Z. Imran; M. Mushtaq; N. Akhtar M. A. Ali; F. Mujeeb (Journal of Animal and Plant Sciences, 2013)
Legumes are very well known for their symbiotic relationships with Rhizobium, responsible for specific structure i.e. nodules on 90% of family Fabaceae and displayed all possible means for improving the fertility of soils. Rhizobium due to its great colonizing ability may be used in non-legumes for improving crop growth. The physiological precursors are cost effective, water soluble and provide hormones continuously. Present study was planned to assess the Rhizobium species of (chickpea, berseem and lentil) with and without L-Tryptophan (L-TRP) on yield parameters of maize. On the basis of auxin biosynthesis potential, isolates of Rhizobium sp (Cp3, Br3 and Lt2) were selected for experimentation. Results revealed that Rhizobium isolates (Cp3, Br3 and Lt2) improved the growth and fodder yield of maize over control and impact was further prominent with the application of L-TRP. Interaction of L-TRP and Rhizobium species (Cp3, Br3 and Lt2) increased the fresh fodder and dry matter yield than their separate application. Increase in fresh fodder and dry matter yield (28.02, 37.89 and 26.88%) and (28.82, 39.36 and 25.73%) was observed with interaction of L-TRP and Rhizobium species (Cp3, Br3 and Lt2), respectively. Study clearly demonstrated that interaction of L-TRP and Rhizobium species (Cp3, Br3 and Lt2) improved the plant NP content, chlorophyll (a and b) content, photosynthetic, transpiration and photo active radiation and plant physical parameters. Results showed that precursor-inoculum interaction is an efficient approach and may be tested in different ecologies.
Keywords: Precursor-inoculum interaction; L-TRP; Rhizobium species; maize